Erosão dos solos após incêndios florestais: avaliação de medidas de mitigação aplicadas em vertentes e em canais, no NW de Portugal - Gonçalves, António Bento (2013)
Portugal is traversed each year by fires, showing a positive trend for an annual increase in their number and in the area scorched, as well as an increase in the recurrence of fires (Ferreira-Leite et al., 2011) and occurrence of large fires (Ferreira- Leite, 2010; Ferreira-Leite et al., 2011, 2013). The development and implementation of measures which promote the reduction of the impacts of forest fires is, therefore, imperative, and should be part of any strategy for forest and soil defense and recovery, especially considering the actual scenario of continuous growth in the number of fires and burnt area (Robichaud, 2009, 2010). This paper therefore seeks to present the measures applied in the study area within the project Soil Protec, relating to channels triggered processes, and the results of preliminary observations concerning the evaluation of the effectiveness of erosion mitigation measures implemented and their cost/benefit ratio.